1996
DOI: 10.1007/bf02055130
|View full text |Cite
|
Sign up to set email alerts
|

Adenocarcinoma arising from a strictureplasty site in Crohn's disease

Abstract: The occurrence of small-bowel cancer in Crohn's disease (CD) is a rare event. The risk seems to be greatest in patients with long-standing disease. Strictureplasty has proved to be a valuable alternative in the management of Crohn's strictures of the small-bowel. Critics and proponents of strictureplasty for selected patients with small-bowel Crohn's disease have voiced their concerns about cancer risk in the strictured or strictureplasty site. To date, there has been no clear or detailed report of such an occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
1
8

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(48 citation statements)
references
References 43 publications
3
36
1
8
Order By: Relevance
“…No câncer do intestino delgado, a localização mais comum é o íleo distal (73 a 76%), ao contrá-rio do que acontece na população geral, em que o duodeno e o jejuno são os segmentos mais acometidos 1,5,12,13,14,15 . A ocorrência desse tumor é maior no sexo masculino (3:1), e a faixa etária dos pacientes no momento do diagnóstico é mais precoce (45 a 50 anos), quando comparados aos carcinomas do intestino delgado (65 anos) 1,2,5,12,15,16 .…”
Section: Discussionunclassified
See 2 more Smart Citations
“…No câncer do intestino delgado, a localização mais comum é o íleo distal (73 a 76%), ao contrá-rio do que acontece na população geral, em que o duodeno e o jejuno são os segmentos mais acometidos 1,5,12,13,14,15 . A ocorrência desse tumor é maior no sexo masculino (3:1), e a faixa etária dos pacientes no momento do diagnóstico é mais precoce (45 a 50 anos), quando comparados aos carcinomas do intestino delgado (65 anos) 1,2,5,12,15,16 .…”
Section: Discussionunclassified
“…Os fatores de risco para o desenvolvimento de câncer em DC não estão ainda adequadamente definidos, mas se aceita a instalação precoce e a longa evolução da doença inflamatória como fatores associados de risco 5,14,16,17 . Na maioria dos casos relatados, o cân-cer instala-se muitos anos após o início dos sintomas, ocorrendo em 79% dos pacientes após 20 anos do iní-cio da DC, e em 53% após 30 anos 6,13,17 .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…One concern with strictureplasty is the risk of cancer developing at that site. Marchetti et al reported the first such case in 1996 [31]. Since then, a few more cases have been reported at strictureplasty sites [32,33].…”
Section: Options For Surgerymentioning
confidence: 99%
“…Double-balloon enteroscopic biopsy of suspicious lesions could increase preoperative diagnosis of early-stage disease, but as noted above, routine use this approach is simply not possible right now. In light of these considerations, along with sporadic reports of adenocarcinoma arising at the site of strictureplasties [85,86], the trend toward wider use of strictureplasty should be regarded with caution, especially in elderly patients or those with long-standing disease. In addition, as suggested by Michelassi himself, any lesion at the site of a strictureplasty that is even vaguely suspicious should be biopsied, and given the non-negligible frequency of carcinoids involving the appendix, appendectomies should always be performed with ileocecal strictureplasties (Fig.…”
Section: Jejunoileal and Ileocolic Crohn's Diseasementioning
confidence: 99%